Development and Validation of Microbiology and Parasitology Laboratory Manual for Science Education - Kennedy A Beltran (Integrated Science Education Journal, 2025)
Purpose of the study: This study aimed to develop and validate a Microbiology and Parasitology Laboratory Manual specifically designed for Science Education students, in alignment with the Commission on Higher Education (CHED) Memorandum Order No. 75, series of 2017. The manual seeks to bridge theoretical knowledge with practical application through structured, inquiry-based laboratory activities that cultivate scientific skills, promote critical thinking, and reinforce adherence to laboratory safety protocols. Methodology: The validation process was conducted in two phases. First, subject matter experts in microbiology, parasitology, and science education evaluated the manual based on content accuracy, instructional clarity, relevance, alignment with CHED competencies, and pedagogical soundness. Their feedback was systematically integrated to enhance the manual’s quality. Second, pilot testing was conducted with science education students to assess usability, engagement, and impact on learning outcomes. Data were collected through expert validation checklists, student perception surveys, and performance assessments during laboratory sessions. Main Findings: Findings revealed that the manual was highly satisfactory across all validation criteria. Quantitative and qualitative results from pilot implementation demonstrated significant improvements in students’ comprehension of microbiological and parasitological concepts, laboratory competencies, and overall engagement. Novelty/Originality of this study: This study offers a discipline-specific, standards-aligned laboratory manual developed for teacher preparation, filling a critical gap in localized instructional materials. It emphasizes not only scientific content but also the pedagogical approaches needed for future educators, contributing to quality enhancement in science teacher education.